La armonización del acceso a la apelación en Europa: modelos comparados y borrador del proyecto ELI/Unidroit - Pérez Ragone, Álvaro (2020)
Access to appeal in models compared with a dogmatic method and a compared one in Germany, United Kingdom, France and Italy is important since members of these systems wrote the draft of the ELI/Unidroit project. The objective of this project is to lay the foundations for the harmonization of the civil process for Europe. This way, it aims to describe each national model, analyze it and, then, at the end of the text, compare it with the mentioned project and the main trends in the matter. This contribution is mainly nourished by comparative legal contributions related to access and the filters of appeal, such as the casting of it as a center, and it’s not intended to cover other aspects of the work in progress. We will see that many aspects that already govern civil processes such as German and Italian are incorporated as proposals. Therefore, the idea is to take stock of the criticisms from the national models and examine how much they are reflected in this draft on appeal.